Carbon Footprinting the Internet - Gombiner, Joel (Consilience, 2011)
The internet is the world’s fastest growing CO2 emitter and tech companies are just beginning to come to terms with their carbon footprints. Using the example of a google search, this article touches on the difficulty of an accurate carbon footprint calculation and raises awareness about the environmental effects of web browsing.